Does firm-level equity return respond to domestic and international monetary policy shocks? a panel data study of Malaysia. - Zulkefly Abdul Karim,; Mohd.Azlan Shah Zaidi,; Bakri Abdul Karim, (Penerbit Universiti Kebangsaan Malaysia, 2011)
This paper examines the effect of domestic and international monetary policy shocks upon malaysian firm level equiry returns in a dynamic panel data framework. The determinant of firm-level equiry return has been estimed using augmented Fama and French (1992,1996)multifactor model. The results of the study revealed that firms stock returns have responded negatively to domestic and international monetary policy shocks. interestingly the effect of domestic monetary policy shocks also have differential effects, having a statistically significant impact on small firms equity returns, but not on large firms stock returns. The effect of domestic monetary policy shocks also varies according to the subsector of the economy in which firms are operating. The effect of international monetary policy upon equity returns is also heterogeneous by firm size and subsector of economic activity.